Cooperation control strategies for China's cross-region pollution in a lake basin based on green reduction cost. (3rd May 2016) - Li, Changmin; Sun, Dong; Xie, Xiaoqiang; Xue, Jian
ABSTRACT: The cross-region water pollution issue has always been the widespread concern around the world. It becomes especially critical for China due to the imbalance relates to environmental costs that have accompanied rapid growth of economy. Though the government makes great efforts to improve it, the potential for water pollution conflict is still great. We consider the problem of determining combined control strategies for China's cross-region lake pollution based on the environmental green costs. The problem is first formulated as a generalized bilevel mathematical program where the upper level consists in each region that reduces environmental green costs including three parts: the reduction cost, pollution permit trade cost and cost of environment damage, while the lower level is represented by pollution permit equilibrium market. Finally, we take an empirical analysis in Taihu lake. The numerical study shows that the minimum costs of both total and regional are obviously superior to the current processing costs, which provides theoretical basis for the price of emission permits. Implications : Today, China's rapid gross domestic product (GDP) growth has come at a very high cost, as real estate prices have skyrocketed, the wealth gap has widened, and environmental pollution has worsened. China's central government is urged to correct the GDP-oriented performance evaluation system that is used to judge administrative region leaders. The cross-region water pollution issue has become a troubling issue that urgently needs to be resolved in China. This paper will not only actively aid efforts to govern Lake Taihu and other cross-region valleys, but it will also provide a supplement for theoretical research on cross-region pollution issues.